2014
DOI: 10.1177/0363546513518004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Irradiation on the Clinical Effectiveness of Allogenic Tissue When Used for Primary Anterior Cruciate Ligament Reconstruction

Abstract: These results suggest that primary ACLRs using nonirradiated allografts may provide superior clinical outcomes than those using low-dose (<2.5 Mrad) irradiated grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 64 publications
(69 reference statements)
0
40
0
1
Order By: Relevance
“…First, the allograft tissue used for hybridization by Burrus et al underwent a low-dose irradiation that may affect the viability of the allograft used. 37 The allograft we used was not irradiated instead using a BioCleanse tissue sterilization process without radiation. 32 In addition, patients with ACL tears were treated by 1of 4 different surgeons using either transtibial or independent femoral drilling, several different femoral fixation devices, and included patients with meniscal injuries that may introduce clinical outcome bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the allograft tissue used for hybridization by Burrus et al underwent a low-dose irradiation that may affect the viability of the allograft used. 37 The allograft we used was not irradiated instead using a BioCleanse tissue sterilization process without radiation. 32 In addition, patients with ACL tears were treated by 1of 4 different surgeons using either transtibial or independent femoral drilling, several different femoral fixation devices, and included patients with meniscal injuries that may introduce clinical outcome bias.…”
Section: Discussionmentioning
confidence: 99%
“…35 Other clinical variables were minimized here as we report results from a single surgeon using common femoral and tibial implants and uniform independent femoral drilling technique comparing autograft hamstring to hybrid soft tissue grafts that used all of the patients' autograft tissue augmented with the minimal amount of allograft to achieve the desired graft size for the implant chosen. In addition, we use nonirradiated soft tissue tibialis allografts when hybridization was indicated as they provide superior clinical outcomes compared with low dose irradiated allografts 37 and preserve a similar retear risk as autografts. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Each application has some disadvantages. In the literature, ethylene-oxide was shown to cause synovitis and irradiation was shown to decrease the strength of the graft 2, 3, 6, 8, 11. It was also reported that irradiated fresh-frozen allografts were more likely to fail than non-irradiated ones 2, 12, 13.…”
Section: Discussionmentioning
confidence: 99%
“…There were 415 patients with irradiated allografts and 1038 with non-irradiated allografts with an average age of 32 years. The study reported that knees with non-irradiated allografts had higher mean Lysholm scores and greater knee stability than those with irradiated allografts [63]. Given this existing literature and data from the MOON Consortium revealing 60 % increased odds of graft failure with every 10-year decrease in patient age, most of the pediatric sports community has moved away from consideration of allograft for ACL reconstruction [64].…”
Section: Graft Considerationsmentioning
confidence: 99%